Estudo do efeito da incorporação de parafinas na precipitação de asfaltenos e na estabilidade de emulsões de petróleos brasileiros - Yanes, José Francisco Romero (2018)
Asphaltene precipitation and emulsion formation have been related with flow assurance in all the stages of crude oil production, with special incidence in the news schemes for oil production and processing. These phenomena depend of temperature, pressure and composition variations. This last variable was studied in this work throughout compositional modifications of brazilian dead oils by including three different paraffins (n-hexadecane, docosane and a commercial paraffinic wax pool). The paraffins were tested in a crude oil P1 (16.5 °API, 6.34 wt% asphaltenes), and analyzed in terms of asphaltene solvency, by tests of solubility using n-heptane as precipitant. The asphaltene precipitation onset was affected by the inclusion of all the paraffins in the same extend, with a maximum diminution in the onset of 4.7 + 0.5 n-heptane wt% for the crude oils modified with 10 wt% of paraffins. Similar results were verified in two different oil P2 (17.7 °API, 6.29 wt% asphaltenes) and P3 (16.7 °API, 1.55 wt% asphaltenes), this last with lower asphaltene content. The solids obtained from the different system were analyzed by FT-IR and it was verified that the alkyl content of the aslphaltene was not affected by the inclusion of heavy paraffins. The precipitation behavior was evaluated using reported thermodynamic models based in modification of regular solution model. The modeling reproduced qualitatively the experimental precipitation behavior and showed the relationship between the influences of the paraffin addition with the asphaltene solvency affectation. The results obtained for the model of the crude oil with lower asphaltene contents suggest that better correlations and experimental treatment of this kind of oils should be proposed. Finally, the crude P1 was emulsified using a synthetic brine and then compared with the behavior of emulsions with crudes modified with 4, 6 and 10 wt% of n-hexadecane and paraffins pool. The modified crudes achieve the stable inclusion of 10 % (v/v) more brine in emulsion, with reduction in the interfacial tension at the same time. These phenomena could be related with the asphaltene solvency affectation noted in this work and the presence of interfacial waxy crystals detected by polarized light optical microscopy.